Self-Acceptance Of Seminarian With Non-Genetic Physical Dissabilities - Baki, Marius Beni (SOLUTION, 2020)
This research aimed to (1) analyzes the process of self-acceptance of seminarian with non-genetic physical disabilities and (2) analyze the aspects that influence self-acceptance. In this research, a phenomenological study was utilized. the Phenomenological study is qualitative research. It is a type of research whose purpose is to seek depth and to gain a detailed understanding of the phenomena being researched. The main concept of phenomenology is meaning. Meaning refers to the essential content that arises from the experience of human consciousness. This happens because the study of phenomenology is a philosophical approach to investigate human experiences. The data gathering was done by using a semi-structural interview. Also besides, the data were analyzed by using data reduction coding. To measure the validity of this research, the researcher used the triangulation technique where the researcher did interviews with several parties related to the subject, such as the informant's close friend and sibling.          The result of this research showed that the process of self-acceptance informant Luis was heavily influenced by the spiritual life, the ability to think realistically, self-perception, the openness in telling the chronology of the disabilities, and the social support from other seminarians in the community and the sibling. Other than that, the attitude of responding to other people's criticism made informant Luis realized that he needed to undergo more processes in controlling emotions. Criticism and other people's opinions can affect one's self-acceptance.